Scalable Video Streaming Based on JPEG2000 Transcoding with Adaptive Rate Control. (8th February 2007) - Vetro, Anthony; Schwenke, Derek; Hata, Toshihiko; Kuwahara, Naoki
Abstract : This paper describes a scalable video streaming system based on JPEG2000 with various modes of streaming. A core function of the proposed system is a low-complexity transcoding technique that adapts the quality and resolution of the scene based on available bandwidth. One key feature of this technique that is important for surveillance applications is that interesting regions of the scene are assigned higher quality than background regions. To cope with varying network conditions, we also present a rate control algorithm that adaptively transcodes stored JPEG2000 frames. The proposed algorithm is designed to improve overall quality over a uniform rate control method by increasing bandwidth utilization, while satisfying buffer constraints and maintaining consistent quality over time. Simulation results confirm the effectiveness of the proposed system and rate control algorithm in terms of both objective measures and subjective evaluation. Complexity is also evaluated.